PREPARING THE ASIAN NON-NATIVE ENGLISH SPEAKER FOR PROFESSIONAL DISCOURSE COMMUNITIES - Michael Guest (Universitas Negeri Padang, 2016)
With an ever-increasing focus upon English for specific purposes (ESP) programs being advanced in East Asia, training both English learners and young in-service professionals to enable their entry into a specific discourse community has become necessary. Without the ability to engage and interact in English within a professional specialty, it will be difficult for any society to maintain pace with, or advance in, the global community. But what are the types of skills, the hallmarks of belonging, that are required for entry into and participation in professional discourse communities (PDCs)? Moreover, what does it mean for the Asian non-native English speaker to enter into such a community? Does this type of internationalization require an abandonment of local norms and subsequent absorption into Anglo-American modes of communication? This paper attempts to answer these questions by drawing upon a compilation of the author’s recent research regarding the management of spoken medical English, both in Japan and Southeast Asia, focusing in particular upon English conference English presentations and in vivo medical workplace discourse. Based upon the author’s previous fieldwork in this area, it will be demonstrated that management of professional discourses does not require conformity to an Anglo-American standard. However, to avoid dependency upon overly localized varieties of English that do not conform to the emerging standards of international discourse communities, particular attention should be paid to the following often underappreciated aspects of international professional discourses, 1) speech event opening gambits and transitions 2) the use of semi-academic formulaic phrases in academic presentations, and 3) the use of ellipsis and other abbreviated forms in the professional workplace. Samples from 1) Medical conference presentations 2) Doctor-Patient history taking, and 3) Nurse-Nurse workplace dialogues will be used to demonstrate the value and importance of each of these features.